EFEKTIFITAS AROMATERAPI JAHE TERHADAP IBU NIFAS UNTUK MENURUNKAN SKOR EDINBURGH POSTPARTUM DEPRESSION SCALE SEBAGAI UPAYA UNTUK MENCEGAH POSTPARTUM BLUES - Fitriana Rakhimah (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2024)
The postpartum period is the period experienced by women after the baby is born until the reproductive organs. The postpartum period is a period of adjustment for a woman to her new role as a parent, so this period usually occurs especially in women who are giving birth for the first time because they do not have experience caring for a baby. The aim of this research is to find out whether there is an effect of giving ginger aromatherapy on reducing Endinburgh Postpartum Depression Scale scores in postpartum mothers as an effort to prevent postpartum blues in the Tegal City Health Center Area. Research is useful for providing information and increasing knowledge in implementing complementary midwifery care, especially in dealing with anxiety in postpartum mothers. The method in this research uses a quasi-experimental design with a pretest posttest with control design. The sample used in this research was 30 postpartum mothers who experienced psychological disorders or postpartum blues who were divided into 2 groups, namely the treatment group and the control group. The results of the study showed that giving ginger aromatherapy was effective in reducing anxiety in postpartum mothers in the Tegal City Health Center Working Area, expressed by a P Value <0.05. Advice that can be given to health workers is to provide education to the public, especially mothers regarding the provision of aromatherapy as a non-pharmacological therapy given to postpartum mothers who experience postpartum blues.